Quantitative structural characterization of phosphatidylinositol phosphates from biological samples - Kim, Su Hee (J Lipid Res, 2017)
The aspects of cellular metabolism controlled by phosphatidylinositol phosphates (PtdInsPs) have been broadly expanded, and these phospholipids have drawn tremendous attention as pleiotropic signaling molecules. PtdInsPs analysis using LC/MS/MS has remained challenging due to the strong hydrophilicity of these lipids. Multiple reaction monitoring (MRM) or a neutral loss scan has been performed to quantitatively measure PtdInsPs after chemical derivatization on the phosphate groups of inositol moieties. Only predefined PtdInsPs can be measured in MRM mode, and fatty acyl compositions of sn-1 and sn-2 positions of PtdInsPs cannot be obtained from a neutral loss scan. In our present study, we developed a simple LC/MS/MS method for structural identification of sn-1 and sn-2 fatty acids of PtdInsPs and their relative quantitation. Precursor ion scans of sn-1 monoacylglycerols (MAGs) of PtdInsPs provided structural information about the lipids, and ammonium adduction enhanced signal intensities of PtdInsPs. The relative amount of observed PtdInsPs in biological samples could be compared using chromatographic peak areas from the neutral loss scans. Using precursor ion scans of sn-1 MAG and neutral loss scans of headgroups, major PtdInsPs in cells and tissues were successfully identified with structural information of sn-1 and sn-2 fatty acids, and their relative amounts in different samples were compared.